Analysis of Customer Satisfaction of Saung Wulan Restaurant Using SERVQUAL Method, Importance Performance Analysis (IPA) and Gap Analysis - Widodo, Purwanto (KnE Social Sciences, 2024)
Restaurant growth in West Java is very rapid at around 12.52% per year. Saung Wulan restaurant is one of the restaurants that applies the traditional concept in Bekasi Regency. This study aims to determine the customer satisfaction of Saung Wulan restaurant. The research was conducted in April 2023 with a sample of Saung Wulan restaurant visitors during that period. The data were analyzed using the SERVQUAL concept, importance performance analysis (IPA), and gap analysis. During the research period, 144 respondents were collected, of which 53.41% were male, age range between 20 - 30 years, 44.32% and 31.82% of high school education. The results of the analysis show that the top priority services for improvement are: The suitability of the menu offered to the order, the speed of the staff in processing orders, and providing careful service. The services that have the highest gap between consumer expectations and the reality received are: Fast serving time, staff responsiveness to customer complaints, and staff speed in processing orders. The implication of the is that Saung Wulan Restaurant needs to prioritize improvements in suitability of the menu to orders, speed in processing orders, and careful service to increase customer satisfaction. Additionally, they need to address the high gap between expectations and reality in terms of serving time, response to customer complaints, and speed in processing orders to improve the overall customer experience. Keywords: gap analysis, importance performance analysis (IPA), SERVQUAL